Troia and the troad: scientific approaches : [ ... the International Symposium "Lebensraum Troia zwischen Ergeschichte und Kultur" was held from 2 - 5 April 2001 in Heidelberg] - Wagner, Günther A.; Pernicka, Ernst; Uerpmann, Hans-Peter (Springer, 2003)
When reconstructing the past, the archaeologist needs to take into account all kinds of relevant information. Where no written sources are available, the natural sciences play an indispensable role. Troia is a remarkable site in this respect. The present excavation project at Troia, under the directorship of Manfred Korfmann, integrates various disciplines including geoarchaeology, archaeobotany, zooarchaeology, anthropology, geophysical prospection as well as chemical and technological studies of metal, stone and pottery. Hardly any other archaeological project is supported so intensely and on such a broad scale by archaeometric investigations as the international research group in Troia. In April 2001 an International Symposium was held in Heidelberg, Germany, with the aim of promoting scientific discussion and providing synopses of the various disciplines engaged in Troia. This volume contains most of the contributions presented at the symposium. Due to its broad natural scientific as well as its cultural-historic scope, not only will the specialist but also the interested layman find the book rewarding
Keywords: Troy (Extinct city) -- Congresses; Konferenzschrift -- 2001 -- Heidelberg; Geschichte; Ausgrabung; Troas; Troja